Answer:
See explanation
Step-by-step explanation:
The coordinate of ABCD is not given; So, I will solve using general coordinates (x,y).
First, ABCD is dilated by 1/3.
The rule is:
[tex](x,y) \to \frac{1}{3}(x,y)[/tex]
This gives
[tex](x,y) \to (\frac{x}{3},\frac{y}{3})[/tex]
Next, it is reflected across y-axis.
The rule is:
[tex](x,y) \to (-x,y)[/tex]
So, we have:
[tex](\frac{x}{3},\frac{y}{3}) \to (-\frac{x}{3},\frac{y}{3})[/tex]
So, the complete transformation is:
[tex](x,y) \to (\frac{x}{3},\frac{y}{3}) \to (-\frac{x}{3},\frac{y}{3})[/tex]
Assume that:
[tex]A = (1,3)[/tex]
The transformation will be:
[tex]A' = (-\frac{1}{3},\frac{3}{3})[/tex]
[tex]A' = (-\frac{1}{3},1)[/tex]